Relações biométricas em povoamentos jovens de Pinus taeda L. na Província de Corrientes, República Argentina - Dacosta, Lourdes Patricia Elias (2008)
This study has as objective to study the biometrical relationships in a Pinus taeda L., young forest located in Santo Tomé region, Corrientes, Argentina, belonging to Bosques del Plata S.A. company. The data were collected in temporary plots with ages varying from 4 to 8 years, and in plots for trunk analysis with ages from 12 to 17 years, originated in 3 natural sites (red hill, brown hill, paddy-soils), obtaining the dominant height, age, diameter, individual volume and artificial form factor information. The regression equations selected to represent hypsometric relationship development, individual volume (v), dominant height (h100), diameter from the average basal area tree (dg), basal area per hectare (G), volume per hectare (V), and artificial form factor (f) were: d h d = 1,63568 + 0,22125. , ln v = −9,40378 + 1,84287. ln d + 0,85244. ln h , h t t 2 100 ln = −0,95979 + 2,88097.ln − 0,52061.ln , 100 2 100 ln dg =1,69872.ln h − 0,21927.ln h , 100 2 100 ln G =1,78627.ln h − 0,16742. ln h , 100 2 lnV = −0,47410 + 0,50158 .ln G + 0,86198 . ln h , d d h d f 0,09956 0,45010.( h ) 0,26882. 1 0,53626. 1 = + 0,3 2 + + . Growth curve analysis from dominant height upon age indicated that there is an ordinary inclination from the regression curves for the trees in each natural studied site. The same pattern was observed among the curves from the three sampling places, allowing to determine monomorphic site index curves. The comparation from site index curves system, with the curves elaborated for Brazilian regions, showed different development in dominant height, obtaining higher growths for Santo Tomé region (Corrientes, Argentine) until the age of 11, later on turning to be lower than them. The obtained information allows to produce yield tables per site index. For site index 12 total yield was 160 m³/ha and, for site index 22 it was de 492 m³/ha, at 12 years, indicating the presence of difference in volume yield potential in region sites. The maximum mean annual increment (MAI) was reached at 10 years, for site indexes 12 and 22, with 14 and 43 m³/ha, respectively.